The effect of obesity upon Health Related Quality of Life (HRQoL): A comparison of the AQoL-8D and SF-36 instruments - Khan, Munir Ahmed; Richardson, Jeff; O'Brien, Paul (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
OBJECTIVES: The objective of this study was to describe and measure the loss of health related quality of life (HRQoL) associated with obesity using two generic instruments. The first of these, the SF-36, is the most widely used and validated HRQoL instrument worldwide. However, it does not provide utility weights and cannot be used to measure quality adjusted life years (QALYs), an increasingly common unit for comparing the effect of health states in economic evaluation studies. The second, the AQoL-8D, is a multi-attribute utility (MAU) instrument which was developed to increase sensitivity of previous MAU instruments to psycho-social dimensions of a health state and to allow the calculation of QALYs. Since the two instruments differ, an important additional objective of the study was to determine the validity of the AQoL-8D as judged by the SF-36, and therefore the confidence which might be placed upon its use in the context of obesity. METHODS: Data were obtained from patients waiting for bariatric surgery who had completed both the SF-36 and AQoL-8D quality of life instruments and a general questionnaire including height, weight, demographic and socio-economic information. For comparative purposes, scores were standardized using results from a representative sample of the general population. The content validity of the AQoL-8D was assessed by comparing it with the dimension scores from the SF-36 and the summary component (physical and mental) scores. Overall scores from the SF-36 and AQoL-8D instruments were regressed upon patient BMI and the results from the AQoL-8D used to estimate the effect of overweight and obesity upon utility and lost QALYs. RESULTS: The comparison of the instruments indicated that the AQoL-8D has good convergent, concurrent and content validity. Using both instruments, obesity was significantly associated with lower scores for 14 of their 16 dimensions. AQoL-8D, in particular, identified a significant decrease in psychological and social health with happiness, self-worth, coping and mental health, all being poorer than in the control group. Regression results implied that a change in BMI from 30 to 50 decreases utility by 0.12 or by 13.8 percent of the average utility for a 25-35 year old. CONCLUSION: AQoL-8D is a valid measure of utility in the context of obesity. Its inclusion of psycho-social effects significantly increases the measured adverse effects of obesity.